The Effect of Combined Guided Imagery and Slow Deep Breathing Relaxation Techniques on Reducing Blood Pressure in Chronic Kidney Disease Patients Undergoing Hemodialysis: A Quasi-Experimental Study - Olivia, Devina Hana; Riyana, Asep; Kuswandi, Asep (PT. Pubsains Nur Cendekia, 2026)
Background: Chronic kidney disease (CKD) can lead to hypertension, especially in patients undergoing hemodialysis. Relaxation techniques, such as Guided Imagery and Slow, Deep Breathing, may help reduce blood pressure. Aims: To assess the effectiveness of the combined Guided Imagery and Slow Deep Breathing relaxation techniques in lowering blood pressure among patients with CKD undergoing hemodialysis. Methods: This study used a quasi-experimental pretest-posttest control group design. A total of 38 patients, 19 in each group, were purposively sampled using specific inclusion and exclusion criteria. The normality of systolic and diastolic blood pressure data was tested using the Shapiro-Wilk test, which indicated a normal distribution. Statistical analysis was performed using paired t-test and independent t-test. Results: The intervention group experienced a mean reduction of 10.11 mmHg in systolic blood pressure (SD = 7.44), while the control group showed a mean change of -7.74 mmHg (SD = 5.50). For diastolic blood pressure, the intervention group decreased by a mean of 9.11 mmHg (SD = 7.36), compared to a change of -7.47 mmHg (SD = 6.28) in the control group. The independent t-test revealed statistically significant differences between groups for both systolic and diastolic blood pressure, with p-values of 0.000 (p < 0.05). These results demonstrate that the combined Guided Imagery and Slow Deep Breathing intervention significantly lowers blood pressure in patients undergoing hemodialysis for chronic kidney disease. Conclusion: The combined relaxation techniques significantly reduce systolic and diastolic blood pressure in CKD patients undergoing hemodialysis, supporting their use as non-pharmacological interventions for hypertension management.